Perancangan Sistem Informasi Persediaan Dan Penjualan Pada CV. Super Makmur Sentosa - William Pranata Kusuma; Jasmir; Lies Aryani (LPPM Universitas Dinamika Bangsa, 2023)
Super Makmur Sentosa is a business engaged in the sale of furniture located in Jambi City. So far, the data collection process is still using the conventional method which uses paper. With this system, problems often occur, namely with too much data on goods, categories and colors that make it difficult to control the inventory of goods owned by the company, errors often occur in recording and calculating sales notes, inventory items that often experience differences due to the inventory calculation process. which is still calculated manually which causes losses. So we need an information system that provides convenience in recording and searching for data on CV. Super Makmur Sentosa. This research has stages, namely problem identification, data collection, system analysis, system design, and report generation. So as to produce a system that can provide convenience in processing inventory data, sales, search and report generation, making it easier for system users to control product inventory data so as to help CV. Super Makmur Sentosa in data processing to be better and orderly.